2021
DOI: 10.3390/su132011518
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Structural and Functional Bacterioplankton Metacommunity along a River under Anthropogenic Pressure

Abstract: Bacteria, an integral part of aquatic ecosystems, are responsible for the circulation of matter and flow of energy. Since bacterioplankton rapidly responds to any natural and human-induced disturbances in the environment, it can serve as a bioindicator of these changes. Knowing factors that shape the microbial community structure may help the sustainable management of the water environment. However, the identification of environmental signals affecting the structure and function of bacterioplankton is still a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In recent years, the high-throughput 16S rRNA gene sequencing method has become more and more common with the characteristics of acquiring a large number of sequence data on microbial communities [7][8][9]. Liao's work has found that neutral and niche processes played different roles in bacterial community assembly between habitat generalists and specialists [10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the high-throughput 16S rRNA gene sequencing method has become more and more common with the characteristics of acquiring a large number of sequence data on microbial communities [7][8][9]. Liao's work has found that neutral and niche processes played different roles in bacterial community assembly between habitat generalists and specialists [10].…”
Section: Introductionmentioning
confidence: 99%
“…Advances in DNA sequencing technologies and bioinformatics have revolutionized the study of the diversity and dynamics of environmental microbial communities [4][5][6]. However, biases can be introduced at almost all stages (i.e., sampling, sample storage and processing, DNA extraction and sequencing) of the experimental process and affect the perception and interpretation of the microbial community [7][8][9][10]. Maintaining consistency in each processing step is therefore essential during a study.…”
Section: Introductionmentioning
confidence: 99%
“…They are often distributed in areas where people gather and have the characteristics of poor water environment capacity and poor water selfpurification capacity. Water is vulnerable to domestic sewage, rain and garbage [3,4]. Urban river pollution is an increasingly serious problem.…”
Section: Introductionmentioning
confidence: 99%